Inventory Management and Financial Performance of Listed Manufacturing Firms in Nigeria - Akinleye, Gideon Tayo; Adesina, Olufemi Dadepo (Journal of Applied And Theoretical Social Sciences, 2024)
Introduction: This study investigates the impact of inventory management on the financial performance of listed manufacturing firms in Nigeria. By examining data from twenty-eight manufacturing firms across Consumer Goods, Industrial Goods, Health Care, and Agricultural sectors, the research focuses on key inventory metrics, including Inventory Conversion Period (INVCP), Accounts Receivable Period (ACRVP), and Accounts Payable Period (ACPP), and their relationship to Return on Assets (ROA). Method: Employing panel data regression analyses, the study compares fixed and random effects models to understand sector-specific influences on financial outcomes. Results or Findings: The findings reveal that inventory management practices vary in significance across sectors, with Consumer Goods and Industrial Goods firms showing a strong dependency on efficient inventory conversion and debt levels for profitability. In contrast, firm size positively influences profitability in the Health Care sector, while Agricultural firms display broader sectoral dependencies. Discussion or Conclusion: These insights underscore the need for tailored inventory management strategies within each sector to optimize financial performance. The study contributes to the contingency theory of inventory management and provides a foundation for sector-specific inventory practices.